Mengidentifikasi Faktor Gizi Pada Pasien Diabetes Mellitus Tipe 2 Di Kota Depok Tahun 2019 - Isti Istianah; Septiani Septiani; Gusti Kumala Dewi (HB PRESS, 2020)
Diabetes mellitus is the second-largest degenerative disease in Indonesia which is influenced by several factors such as obesity, low physical activity, and poor diet. This study aims to identify nutritional factors in 77 types 2 diabetes mellitus patients in Depok by using a cross-sectional descriptive research design. This study uses a purposive sampling technique with Inclusion and Exclusion Criteria, analyzed using univariate analysis. The results were mostly female respondents 84.4%, aged 51-60 years 76.7%, nutritional status of obesity 44.2%, high school education level 40.3%, respondents not working 68.8%, income level Rp 1,000,000, - up to Rp 2,000,000 per month 39%, and respondents who consumed 87% of the drug, when the blood sugar level (GDS) was 71.4%, breakfast frequency was 72.7%, strength of muscle mass was weak 51.9%. Moderate physical activity 59.7%, moderate GI consumption 64.9%, moderate category BG consumption 48.1% and central obesity 75.3%. This research concludes that low nutritional factors can increase the risk of type II DM in Cimanggis Health Center, Depok City in 2019.